2012
DOI: 10.1007/s11242-012-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Darcy–Forchheimer Law for Shear-Thinning Fluids and Validation via Pore-Scale Flow Simulations

Abstract: Flow of non-Newtonian fluids through porous media at high Reynolds numbers is often encountered in chemical, pharmaceutical and food as well as petroleum and groundwater engineering and in many other industrial applications. Under the majority of operating conditions typically explored, the dependence of pressure drops on flow rate is non-linear and the development of models capable of describing accurately this dependence, in conjunction with non trivial rheological behaviours, is of paramount importance. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
76
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 62 publications
9
76
0
1
Order By: Relevance
“…(5) are neglected and the momentum balance equation is applied to a simple one-dimensional problem, the original phenomenological (linear) law developed by Darcy is retrieved. At higher superficial velocities, the Darcy-Forchheimer law is generally used [5][6][7], and the friction coefficient is assumed to be function of the fluid superficial velocity: γ = μ /ρα + β|V|, where now α and β are the two Darcy-Forchheimer parameters. The application of the Darcy-Forchheimer law to a simple one-dimensional problem, again neglecting the time derivative and the inertial terms, results in a quadratic law, often written in the following form:…”
Section: Introductionmentioning
confidence: 99%
“…(5) are neglected and the momentum balance equation is applied to a simple one-dimensional problem, the original phenomenological (linear) law developed by Darcy is retrieved. At higher superficial velocities, the Darcy-Forchheimer law is generally used [5][6][7], and the friction coefficient is assumed to be function of the fluid superficial velocity: γ = μ /ρα + β|V|, where now α and β are the two Darcy-Forchheimer parameters. The application of the Darcy-Forchheimer law to a simple one-dimensional problem, again neglecting the time derivative and the inertial terms, results in a quadratic law, often written in the following form:…”
Section: Introductionmentioning
confidence: 99%
“…However, the recent research results (Tosco et al, 2013) indicate that the inertial effect and coefficients are demonstrated to be independent of the viscous properties of the fluids, and the above Equation (10) may be directly used in Equation (2).…”
Section: Mathematical Modelmentioning
confidence: 99%
“…To give an example, surfactant flooding targets the residual oil by enhancing the microscopic displacement efficiency. Polymer flooding on the other hand mainly targets the bypassed oil by improving the macroscopic sweep efficiency (Reuvers and Golombok 2009;van der Plas and Golombok 2015). There is also an effect on the microscopic displacement efficiency which can have also significant economic benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the polymer formulation, these effects sometimes play a significant role in controlling the mobility reduction factor (Sorbie 1991;Rodriguez et al 2014). The increase in in situ viscosity is a combination of rheological effects such as shear-dependent fluid viscosity, extensional viscosity (Koroteev et al 2013;van der Plas and Golombok 2015) and visco-elasticity (Wang et al 2010). Polymer in general and more specifically aqueous solutions of hydrosoluble polymer including HPAM exhibit a shear rate-dependent bulk viscosity (Delshad et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation